Interferometry of class i methanol masers, statistics and the distance scale - Voronkov, M.; Breen, S.; Ellingsen, S.; Jordan, Christopher (2017)
The Australia Telescope Compact Array (ATCA) participated in a number of survey programs to search for and image common class I methanol masers (at 36 and 44 GHz) with high angular resolution. In this paper, we discuss spatial and velocity distributions revealed by these surveys. In particular, the number of maser regions is found to fall off exponentially with the linear distance from the associated young stellar object traced by the 6.7-GHz maser, and the scale of this distribution is 263±15 milliparsec. Although this relationship still needs to be understood in the context of the broader field, it can be utilised to estimate the distance using methanol masers only. This new technique has been analysed to understand its limitations and future potential. It turned out, it can be very successful to resolve the ambiguity in kinematic distances, but, in the current form, is much less accurate (than the kinematic method) if used on its own.